In the fiscal control is the mitigation of the corruption (2015)
Despite Transparency strategies and anticorruption policies being implemented in politics by the Colombian national government; there is still evidence of weakness from local authorities where corruption is prevalent, especially in different aspects such as public procurement, tax control and human resources management. For this reason, this phenomenon has caused citizens to distrust management control and the efficient use of resources. People started to show some kind of apathy regarding control and process’ verification; which they have to be aware of in order to demand an efficient public administration. That eventually becomes evident in the election of leaders with voting abstention. However, citizens’ commitment is key to transform and develop the necessary control that enables a change in public administration; where they apply a specific mechanism that allows social, economic and environmental development in Colombia to prevent corruption.